Management of a Concealable Stigmatized Identity: A Qualitative Study of Concealment, Disclosure, and Role Flexing Among Young, Resilient Sexual and Gender Minority Individuals. Issue 6 (12th May 2017) - Bry, Laura Jane; Mustanski, Brian; Garofalo, Robert; Burns, Michelle Nicole
ABSTRACT: Disclosure of a sexual or gender minority status has been associated with both positive and negative effects on wellbeing. Few studies have explored the disclosure and concealment process in young people. Interviews were conducted with 10 sexual and/or gender minority individuals, aged 18–22 years, of male birth sex. Data were analyzed qualitatively, yielding determinants and effects of disclosure and concealment. Determinants of disclosure included holding positive attitudes about one's identity and an implicit devaluation of acceptance by society. Coming out was shown to have both positive and negative effects on communication and social support and was associated with both increases and decreases in experiences of stigma. Determinants of concealment included lack of comfort with one's identity and various motivations to avoid discrimination. Concealment was also related to hypervigilance and unique strategies of accessing social support. Results are discussed in light of their clinical implications.